Effect of single atomic layer graphene film on the thermal stability and hydrogen permeation of Pd-coated Nb composite membrane. (12th February 2022) - Guo, Yakun; Guo, Ying; Zou, Dongli; Pan, Qifa; Jiang, Chunli; Li, Yingjun; Chen, Chang'an
Abstract: Pd coated Nb-base composite membranes are preferable in the fields of hydrogen permeation. However, the rapid reduction of hydrogen permeability caused by high-temperature interfacial diffusion of Pd and Nb atoms hinders their large-scale application. In this paper, a single atomic layer graphene film was used for improving the thermal stability of a hydrogen-permeable composite membrane comprising a Pd coating on the Nb substrate. First, the graphene film was transferred onto the surface of the "clean" niobium substrate. Then a thin palladium coating was deposited on it by magnetron sputtering to form the niobium/graphene/palladium (Nb/Gr/Pd) composite membrane. The interfacial stability was evaluated in the temperature range of 673–973 K under vacuum, and the hydrogen permeation behavior was studied by gas-driven permeation method at 573–823 K. The results show that the single atomic layer graphene film can effectively compress the interdiffusion of Pd coating and Nb substrate and achieve a good hydrogen permeability below 823 K. However, it would be broken due to the micro-deformation of Nb substrate, the high mobility of Pd atoms, and the grain growth at a higher temperature. Therefore, it is concluded that the single atomic layer graphene film is unsuitable as an intermediate hindering layer for Nb-based hydrogen-permeable membranes. Highlights: The interdiffusion of Pd and Nb hinders hydrogen permeation. Single-layer graphene film can suppress the interdiffusion of Pd and Nb atoms. The hydrogen can permeate through Pd/Gr/Nb/Gr/Pd membranes. Graphene films will break under higher temperatures.